2019
DOI: 10.1101/530014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA interactions with CTCF are essential for its proper function

Abstract: The function of the CCCTC-binding factor (CTCF) in the organization of the genome has become an important area of investigation, but the mechanisms of how CTCF dynamically contributes to genome organization is not clear. We previously discovered that CTCF binds to large numbers of endogenous RNAs; promoting its oligomerization. Here we found that inhibition of transcription or interfering with CTCF ability to bind RNA through mutations of two of its 11 zinc fingers that are not involved with CTCF binding to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…9A,B). Given that the stability of CTCF on chromatin requires its RNA binding activity (Hansen et al 2018;Saldana-Meyer et al 2019), we suspect that disrupting this latter activity would give rise to similar developmental defects.…”
Section: Boundaries To Spreadingmentioning
confidence: 99%
“…9A,B). Given that the stability of CTCF on chromatin requires its RNA binding activity (Hansen et al 2018;Saldana-Meyer et al 2019), we suspect that disrupting this latter activity would give rise to similar developmental defects.…”
Section: Boundaries To Spreadingmentioning
confidence: 99%
“…Recently, we found that the maternal expression of Meg3, and possibly the lncRNA itself, prevents activation of Dlk1 as well (25). We hypothesise that the two mechanisms are linked, with either the Dlk1-Meg3 sub-TAD focusing or constraining the repressive function of the Meg3 expression or transcript, or conversely, with maternal Meg3 expression facilitating CTCF recruitment or its stability of binding at the DMR, possibly through direct RNA-CTCF contacts (32,33).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we also found human lncRNA JPX present as one of the RNA transcripts pulled-down with human CTCF by PAR-CLIP from human bone osteosarcoma U2OS cells (Supplementary data from (Saldaña-Meyer et al, 2014)). Moreover, RNA-binding regions (RBR) in CTCF have been recently reported and shown to be essential for the molecular interaction and function of CTCF in mouse and human cells (Hansen et al, 2018;Saldana-Meyer et al, 2019), which confirm CTCF binding to endogenous RNAs and the functional importance of CTCF-RNA binding in gene regulation. Our evidence of direct binding of CTCF to human JPX RNA similar to CTCF-Jpx lncRNA interaction in the mouse thus supports the functional importance and conservation of human JPX to its mouse homolog.…”
Section: Rna Functionmentioning
confidence: 94%